The Influence Of Natural Environment Usage On Student Learning Outcomes In The Concept Of Biodiversity - A. Hadian Pratama Hamzah; Nurhasanah Nurahasana (Mudir : Jurnal Manajemen Pendidikan, 2023)
With the aid of quantitative techniques (a Quase Experiment), this study seeks to ascertain the impact of the Environmental Approach on student learning outcomes. A sample was took from two distinct classes from one of the high schoolS were used for this study. The first class served as the experimental class that received instruction using an environmental approach, while the second class served as the control class that solely received instruction via lectures. A multiple-choice exam uses 35 questions of alternate responses was the research tool employed. The study's findings that the environmental approach significantly influences how students understand the idea of biodiversity.